Preparation method of hollow-structure TiO2 or TiO2 / ZnO heterojunction and application of hollow-structure TiO2 or TiO2 / ZnO heterojunction in ultraviolet detector
By using hollow structure TiO2 and three-dimensional hedgehog-shaped hollow structure TiO2/ZnO heterojunction in ultraviolet detectors, the problem of insufficient detection performance of TiO2 materials is solved, the photoelectric conversion efficiency and detection sensitivity are improved, and a self-energized ultraviolet detector is realized.
Patent Information
- Application Number
- CN202411746685.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-21
AI Technical Summary
The detection performance of TiO2 materials in ultraviolet detectors is insufficient, mainly due to the low specific surface area and the rapid recombination of photogenerated carriers, resulting in a reduced photoelectric conversion efficiency.
The solution method was used to synthesize TiO2 with hollow structure and TiO2/ZnO heterojunction with three-dimensional hedgehog-shaped hollow structure, and disperse it in a deionized aqueous solution, and evenly apply it on the FTO conductive glass to form a working electrode, and combine it with the iodine electrolyte to construct a self-energized ultraviolet detector.
By increasing the specific surface area of the material, improving the light absorption capacity, and effectively separating photogenerated carriers through TiO2/ZnO heterojunction, the photoelectric conversion efficiency and detection sensitivity of the ultraviolet detector are improved, and the self-energized detection characteristics are achieved.
Smart Images

Figure CN119660788A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of semiconductor detection materials and preparation thereof, and in particular relates to a preparation method of hollow-structured TiO2 and TiO2 / ZnO heterojunction and application thereof in ultraviolet detectors. Background Art
[0002] Ultraviolet detectors have been widely developed and applied in various fields such as civil and military, such as biological detection, fire monitoring, missile tracking and ultraviolet communication. At present, many ultraviolet detectors need an external load power supply to work together to obtain good detection performance. Since self-powered ultraviolet detectors do not require an external power supply, they have the advantages of low energy consumption, miniaturization and long-term operation, and have become a research hotspot in recent years. At present, traditional wide bandgap semiconductor materials, such as GaN, GaAs, SiC and AlN, have become hot candidate materials for the preparation of ultraviolet detectors due to their suitable bandgap width, good radiation resistance and high integration. However, the preparation of these traditional wide bandgap semiconductors often requires complex equipment, high production costs, and harsh growth conditions (such as high temperature, high vacuum, etc.), which restricts the large-scale sustainable development of the ultraviolet detection field.
[0003] Among many detector materials, TiO2 has a suitable band gap width (3.2eV), can achieve good absorption of ultraviolet light, and is non-toxic, low in preparation cost, and has good carrier transport capabilities. It is considered to be one of the most promising ultraviolet detection materials. However, TiO2 materials have certain limitations. Its specific surface area is relatively low, resulting in a limited area for ultraviolet light to contact and act on the material, which affects TiO2's ability to absorb ultraviolet light. In addition, TiO2 also faces the problem of rapid recombination of photogenerated carriers, which will lead to a reduction in the number of carriers that can participate in the photoelectric conversion process and generate effective electrical signals, reducing the photoelectric conversion efficiency of the detector, thereby affecting its key performance indicators such as the photoresponse current to ultraviolet light and detection sensitivity, and ultimately limiting the detection performance of TiO2 ultraviolet detectors. Therefore, it is of great significance to develop a simple, convenient and low-cost method for preparing TiO2 heterojunctions and apply them to ultraviolet detectors. Summary of the invention
[0004] The purpose of the present invention is to solve the problem of insufficient detection performance of TiO2 materials in the application of ultraviolet detectors, and to provide a method for preparing hollow-structured TiO2 and TiO2 / ZnO heterojunctions and their applications in ultraviolet detectors. The present invention uses a convenient and low-cost solution method to synthesize hollow-structured TiO2 and three-dimensional hedgehog-shaped hollow-structured TiO2 / ZnO heterojunctions; the hollow-structured TiO2 and three-dimensional hedgehog-shaped hollow-structured TiO2 / ZnO heterojunction materials are dispersed in a deionized water solution, and uniformly coated on the conductive surface of FTO conductive glass to prepare a working electrode, a Pt electrode, ITO conductive glass or FTO conductive glass is selected as a counter electrode, the working electrode and the counter electrode are connected by a heat-sealed film, and an iodine electrolyte is filled in the cavity between the two, so as to obtain a UV detector with good performance, which can realize the characteristics of self-powered detection without an external power supply, and is further applied to the field of ultraviolet detection.
[0005] The objective of the present invention is achieved through the following technical solutions:
[0006] A hollow structured TiO2, wherein the overall appearance of the TiO2 is spherical, cubic or dodecahedral, the interior of the TiO2 is a hollow structure, and the shell thickness is 10 to 400 nm.
[0007] A method for preparing hollow-structured TiO2, the specific steps of the method are:
[0008] Step 1: adding sodium hydroxide to a solution containing Cu ions and a certain amount of polyvinyl pyrrolidone, and then adding ascorbic acid, reacting at room temperature to 60° C. for 10 min to 5 h, centrifuging and naturally drying to obtain a spherical, cubic or dodecahedral Cu2O nanostructure;
[0009] Step 2: adding Cu2O to a mixed solution of 0.02-0.2 mol / L ammonium fluorotitanate and 0.06-0.6 mol / L boric acid, heating in a water bath at room temperature to 60°C for 1-10 hours, centrifuging and drying naturally at room temperature, and then annealing in an air atmosphere at a temperature of 200-600°C for 1-3 hours;
[0010] Step 3: Add the annealed sample to an acidic solution for 30 min to 3 h, wash it by centrifugation with deionized water and alcohol for 1-5 times, and dry it naturally at room temperature to obtain a hollow structured TiO2.
[0011] Furthermore, in step 1, the concentration of the Cu ion solution is 0.02-0.2 mol / L, the concentration of sodium hydroxide is 0.02-2 mol / L, the amount of polyvinyl pyrrolidone added is 0-8 g, and the amount of ascorbic acid added is 0.001-0.01 mol.
[0012] A TiO2 / ZnO heterojunction based on a hollow structure. The heterojunction is composed of ZnO nanorods and TiO2 with a hollow structure. The ZnO nanorods grow on the outer surface of the TiO2 with a hollow structure, and the whole presents a three-dimensional hedgehog-shaped hollow structure.
[0013] A method for preparing a hollow structure TiO2 / ZnO heterojunction, the specific steps of the method are:
[0014] Step 1: prepare 0.01-0.05 mol / L sodium hydroxide ethanol solution and 0.01-0.05 mol / L zinc acetate ethanol solution, mix them, heat them in a water bath at 50-90° C. for 1-5 h, and let them stand for 6-18 h to obtain a ZnO seed solution;
[0015] Step 2: Add the hollow structure TiO2 into the ZnO seed solution and react at room temperature for 10 minutes to 3 hours;
[0016] Step 3: Prepare a mixed solution of 0.01-0.1 mol / L zinc nitrate and hexamethylenetetramine as a growth solution, add the solution in step 2 to the growth solution, heat in a water bath at 60-95° C. for 5 min-10 h, centrifuge and naturally dry to obtain a TiO2 / ZnO heterojunction.
[0017] Furthermore, the hollow structure TiO2 described in step 2 is a TiO2 hollow sphere, a TiO2 hollow cube, or a TiO2 hollow dodecahedron.
[0018] An application of a hollow TiO2 structure in an ultraviolet detector, using FTO conductive glass loaded with a hollow TiO2 structure material as a working electrode of the detector, connecting the working electrode with a counter electrode (Pt electrode, ITO conductive glass or FTO conductive glass) at 100-180° C. using a heat-sealing film, and filling the middle cavity with an iodine electrolyte to obtain an ultraviolet detector based on a hollow TiO2 structure;
[0019] The preparation method of the TiO2 hollow structure working electrode is as follows: the TiO2 hollow structure material is dispersed in deionized water, and uniformly coated on the conductive surface of FTO conductive glass by drop casting, and the coating and drying are repeated 3 to 10 times to obtain the TiO2 hollow structure working electrode.
[0020] Furthermore, the TiO2 hollow structure working electrode is one of a TiO2 hollow sphere working electrode, a TiO2 hollow cube working electrode or a TiO2 hollow dodecahedron working electrode.
[0021] The invention discloses an application of a hollow structure TiO2 / ZnO heterojunction in an ultraviolet detector, wherein an FTO conductive glass loaded with the hollow structure TiO2 / ZnO heterojunction is used as a working electrode of the detector, the working electrode is connected to a counter electrode (Pt electrode, ITO conductive glass or FTO conductive glass) at 100-180° C. by using a heat-sealing film, and an iodine electrolyte is filled in the middle cavity to obtain an ultraviolet detector based on the hollow structure TiO2 / ZnO heterojunction.
[0022] The preparation method of the TiO2 / ZnO heterojunction working electrode is as follows: dispersing the TiO2 / ZnO heterojunction material in deionized water, uniformly coating it on the conductive surface of FTO conductive glass by drop casting, repeating the coating and drying for 3 to 10 times, and obtaining the TiO2 / ZnO heterojunction working electrode.
[0023] Furthermore, the TiO2 / ZnO heterojunction working electrode is one of a TiO2 hollow sphere / ZnO nanorod working electrode, a TiO2 hollow cube / ZnO nanorod working electrode or a TiO2 hollow dodecahedron / ZnO nanorod working electrode.
[0024] The advantages of the present invention compared to the prior art are:
[0025] A method for preparing a three-dimensional hollow structure TiO2 with a simple process and low cost has been developed. A variety of hollow structure TiO2 with large specific surface areas, such as hollow spheres, hollow cubes and hollow dodecahedrons, can be synthesized. The large cavity inside the material makes the material have a larger specific surface area, which is more conducive to the scattering and reflection of ultraviolet light inside the hollow structure material, thereby achieving better light absorption capacity. At the same time, a method for preparing a three-dimensional hedgehog-shaped hollow structure TiO2 / ZnO heterojunction is provided. One-dimensional ZnO nanorods are composited on the surface of the hollow structure TiO2, which not only maintains the advantage of the large specific surface area of the hollow structure, but also forms a unique three-dimensional hedgehog-shaped hollow structure with the one-dimensional ZnO nanorods. The TiO2 / ZnO heterojunction formed at the same time can effectively separate photogenerated carriers.
[0026] In addition, a method for preparing a hollow structure TiO2 and a three-dimensional hedgehog-shaped hollow structure TiO2 / ZnO heterojunction ultraviolet detector is designed, and an ultraviolet detector with good detection performance can be obtained by changing the morphology, size, shell thickness of the hollow structure TiO2 and the length and diameter of the ZnO nanorods. The present invention successfully realizes the synthesis of the hollow structure TiO2 / ZnO heterojunction and the preparation of the ultraviolet detector, which is suitable for large-scale production and application, and has broad application prospects in the field of ultraviolet detection. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is the SEM image of TiO2 hollow spheres.
[0028] Figure 2 This is the SEM image of TiO2 hollow cube.
[0029] Figure 3 This is the SEM image of TiO2 hollow sphere / ZnO nanorod heterojunction.
[0030] Figure 4 This is the time-resolved current curve of the TiO2 hollow ball UV detector under UV light irradiation.
[0031] Figure 5 This is the time-resolved current curve of the TiO2 hollow sphere / ZnO nanorod heterojunction UV detector under ultraviolet light irradiation. DETAILED DESCRIPTION
[0032] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and embodiments, but is not limited thereto. Any modification or equivalent replacement of the technical solution of the present invention that does not depart from the spirit and scope of the technical solution of the present invention should be included in the protection scope of the present invention.
[0033] Embodiment 1:
[0034] A method for preparing TiO2 hollow spheres, the method steps are as follows:
[0035] Step 1: First prepare 25 ml of a mixed solution of 0.1 mol / L NaOH and 0.05 mol / L copper sulfate, then add 0.001 mol ascorbic acid under rapid stirring, and when the solution color turns light yellow, continue to stir at a constant speed for 30 min at room temperature, centrifuge and dry naturally to obtain Cu2O nanospheres;
[0036] Step 2: First, prepare 25 ml of a mixed solution of 0.02 mol / L ammonium fluorotitanate and 0.06 mol / L boric acid, stir evenly, then directly add the Cu2O nanosphere powder to the mixed solution, stir evenly, react at 45°C for 2 h, centrifuge and dry naturally at room temperature, and then anneal in an air atmosphere at 400°C for 1 h;
[0037] Step 3: Add the annealed sample to 0.5 mol / L boric acid solution and react for 2 h. Wash it by centrifugation for 3 times with deionized water and alcohol, and dry it naturally at room temperature to obtain TiO2 hollow spheres.
[0038] SEM images of TiO2 hollow spheres Figure 1 As shown, it can be observed that the TiO2 hollow spheres are evenly distributed, with a size of about 300 to 700 nm, and a hollow spherical structure can be clearly seen from the broken part.
[0039] Embodiment 2:
[0040] A method for preparing a TiO2 hollow cube, the method comprising the following steps:
[0041] Step 1: Prepare 100 ml of 0.1 mol / L copper chloride solution, stir evenly, then add 10 ml of 2 mol / L sodium hydroxide solution, stir for 0.5 h, then drop 10 ml of 0.6 mol / L ascorbic acid solution into the dark brown solution, and react in a water bath at 55° C. for 3 h; wash and centrifuge the solution after the reaction, and dry it at room temperature to obtain Cu2O nanocubes;
[0042] Step 2 and step 3 are the same as step 2 and step 3 in Example 1.
[0043] Figure 2 This is the SEM image of the TiO2 hollow cube. It can be observed that the prepared TiO2 hollow cube has a regular shape and a cubic structure with a size of about 800 to 1200 nm. From the broken parts in the image, it can be obviously found that the inside of the cube is hollow, which indicates that the TiO2 hollow cube was successfully obtained.
[0044] Embodiment 3:
[0045] A method for preparing a TiO2 hollow sphere / ZnO nanorod heterojunction, the method comprising the following steps:
[0046] Step 1, prepare 10 ml of 0.01 mol / L sodium hydroxide ethanol solution and 25 ml of 0.01 mol / L zinc acetate ethanol solution, mix them, heat them in a water bath at 50° C. for 3 h, and let them stand for 10 h to obtain a ZnO seed solution;
[0047] Step 2: Add the TiO2 hollow spheres (0.05 g) obtained in Example 1 into the ZnO seed solution and stir at room temperature for 10 min;
[0048] Step 3: prepare 30 ml of a 0.04 mol / L mixed solution of zinc nitrate and hexamethylenetetramine as a growth solution, add the solution obtained in step 2 to the growth solution, heat in a water bath at 85°C for 5 h, centrifuge and naturally dry to obtain a TiO2 hollow sphere / ZnO nanorod heterojunction.
[0049] SEM images of TiO2 hollow sphere / ZnO nanorod heterojunction are shown in Figure 4 As shown in the figure, it can be seen that the TiO2 hollow spheres are completely wrapped by ZnO nanorods, and the overall morphology maintains a hedgehog-like structure. In addition, the diameter of the hedgehog sphere is about 1 μm, and the ZnO nanorods are about 300 nm.
[0050] Embodiment 4:
[0051] A method for preparing a TiO2 hollow sphere ultraviolet detector, the method steps are as follows:
[0052] Step 1: Disperse TiO2 hollow spheres in deionized water, and evenly coat them on the conductive surface of FTO conductive glass by drop casting, repeat coating and drying for 5 times to obtain a TiO2 hollow sphere working electrode;
[0053] Step 2: The working electrode and the FTO conductive glass counter electrode are hot-pressed at 140°C for 20 seconds through a heat-sealing film to connect the two electrodes, and iodine electrolyte is injected into the cavity of the device to obtain a TiO2 hollow sphere UV detector.
[0054] Using 365nm light as the simulated UV light source, the detection performance of the TiO2 hollow sphere UV detector was tested with a Keithley 2400 digital source meter without external bias (0V). Figure 4 It is clearly observed that the dark current of the detector is almost zero in the absence of UV light; when exposed to UV light, the photoresponse current rises from the initial value to 0.44μA, and quickly drops to the initial value after the UV light is turned off, indicating that the detector responds quickly to UV light energy. After repeating the on / off cycle 10 times, the device exhibits the same regularity and there is no obvious change in the photocurrent, indicating that the detector has good stability and self-powered detection characteristics.
[0055] Embodiment 5:
[0056] A method for preparing a TiO2 hollow sphere / ZnO nanorod heterojunction ultraviolet detector, the method steps are as follows:
[0057] The TiO2 hollow sphere / ZnO nanorod heterojunction synthesized in Example 3 was treated according to the device preparation process in Example 4 to obtain an ultraviolet detector based on the TiO2 hollow sphere / ZnO nanorod heterojunction.
[0058] Using 365nm light as a simulated UV light source, the detection performance of the TiO2 hollow sphere / ZnO nanorod heterojunction UV detector was tested. The results are as follows: Figure 5 As shown. In the absence of light, the detector has almost no response current; after turning on the ultraviolet light, the photocurrent can quickly increase from the initial state to 7.39μA. Once the ultraviolet light is turned off, the photocurrent quickly drops to the initial state, and it shows a similar current change law in the 10 cycles of turning on / off the ultraviolet light. And no external voltage is applied during the photoelectric detection test, indicating that the prepared detector has self-powered characteristics.
Claims
1. A hollow structure TiO2, characterized in that The overall appearance of the TiO2 is spherical, cubic or dodecahedral, the interior of which is a hollow structure, and the shell thickness is 10 to 400 nm.
2. A method for preparing the hollow structured TiO2 according to claim 1, characterized in that The specific steps of the method are: Step 1: adding sodium hydroxide to a solution containing Cu ions and polyvinyl pyrrolidone, and then adding ascorbic acid, reacting at room temperature to 60° C. for 10 min to 5 h, centrifuging and naturally drying to obtain a spherical, cubic or dodecahedral Cu2O nanostructure; Step 2: adding Cu2O to a mixed solution of 0.02-0.2 mol / L ammonium fluorotitanate and 0.06-0.6 mol / L boric acid, heating in a water bath at room temperature to 60°C for 1-10 hours, centrifuging and drying naturally at room temperature, and then annealing in an air atmosphere at a temperature of 200-600°C for 1-3 hours; Step 3: Add the annealed sample to an acidic solution for 30 min to 3 h, wash it by centrifugation with deionized water and alcohol for 1-5 times, and dry it naturally at room temperature to obtain a hollow structured TiO2.
3. The method for preparing the hollow structured TiO2 according to claim 2, characterized in that: In step 1, the concentration of the Cu ion solution is 0.02-0.2 mol / L, the concentration of sodium hydroxide is 0.02-2 mol / L, the amount of polyvinyl pyrrolidone added is 0-8 g, and the amount of ascorbic acid added is 0.001-0.01 mol.
4. A hollow structure-based TiO2 / ZnO heterojunction, characterized in that The heterogeneous structure is composed of ZnO nanorods and TiO2 with a hollow structure. The ZnO nanorods grow on the outer surface of the TiO2 with a hollow structure, and the whole structure presents a three-dimensional hedgehog-shaped hollow structure.
5. A method for preparing the hollow structure TiO2 / ZnO heterojunction according to claim 4, characterized in that The specific steps of the method are: Step 1: prepare 0.01-0.05 mol / L sodium hydroxide ethanol solution and 0.01-0.05 mol / L zinc acetate ethanol solution, mix them, heat them in a water bath at 50-90° C. for 1-5 h, and let them stand for 6-18 h to obtain a ZnO seed solution; Step 2: Add the hollow structure TiO2 into the ZnO seed solution and react at room temperature for 10 minutes to 3 hours; Step 3: Prepare a mixed solution of 0.01-0.1 mol / L zinc nitrate and hexamethylenetetramine as a growth solution, add the solution obtained in step 2 to the growth solution, heat in a water bath at 60-95° C. for 5 min-10 h, centrifuge and naturally dry to obtain a TiO2 / ZnO heterojunction.
6. The method for preparing a hollow structure TiO2 / ZnO heterojunction according to claim 5, characterized in that: The hollow structure TiO2 described in step 2 is TiO2 hollow sphere, TiO2 hollow cube, TiO2 hollow dodecahedron.
7. An application of a TiO2 hollow structure in an ultraviolet detector, characterized in that: Using FTO conductive glass loaded with TiO2 hollow structure material as the working electrode of the detector, using a heat-sealing film to connect the working electrode with a counter electrode (Pt electrode, ITO conductive glass or FTO conductive glass) at 100-180°C, filling the middle cavity with iodine electrolyte, and obtaining a UV detector based on TiO2 hollow structure; The preparation method of the TiO2 hollow structure working electrode is as follows: the TiO2 hollow structure material is dispersed in deionized water, and uniformly coated on the conductive surface of FTO conductive glass by drop casting, and the coating and drying are repeated 3 to 10 times to obtain the TiO2 hollow structure working electrode.
8. An application of a TiO2 hollow structure in an ultraviolet detector, characterized in that: The TiO2 hollow structure working electrode is one of a TiO2 hollow sphere working electrode, a TiO2 hollow cube working electrode or a TiO2 hollow dodecahedron working electrode.
9. Application of a hollow structure TiO2 / ZnO heterojunction in an ultraviolet detector, characterized in that: Using FTO conductive glass loaded with hollow structure TiO2 / ZnO heterojunction as the working electrode of the detector, connecting the working electrode with the counter electrode (Pt electrode, ITO conductive glass or FTO conductive glass) at 100-180°C using a heat-sealing film, and filling the middle cavity with iodine electrolyte to obtain a UV detector based on the hollow structure TiO2 / ZnO heterojunction; The preparation method of the TiO2 / ZnO heterojunction working electrode is as follows: dispersing the TiO2 / ZnO heterojunction material in deionized water, uniformly coating it on the conductive surface of FTO conductive glass by drop casting, repeating the coating and drying for 3 to 10 times, and obtaining the TiO2 / ZnO heterojunction working electrode.
10. Application of a hollow TiO2 / ZnO heterojunction in a self-powered ultraviolet detector, characterized in that: The TiO2 / ZnO heterojunction working electrode is one of a TiO2 hollow sphere / ZnO nanorod working electrode, a TiO2 hollow cube / ZnO nanorod working electrode or a TiO2 hollow dodecahedron / ZnO nanorod working electrode.